Pediatric dysphagia : etiologies, diagnosis, and management - Willging, Jay Paul; Miller, Claire Kane; Cohen, Aliza P. (Plural Publishing, Inc., 2020)
"Pediatric Dysphagia: Etiologies, Diagnosis, and Management is a comprehensive professional reference on the topic of pediatric feeding and swallowing disorders. Given that these disorders derive from abnormalities in the function and/or structure of the airway and digestive systems, multiple clinical specialists may be involved in the evaluation and management of affected children at any given point in time. This text therefore includes significant contributions from a wide range of experts in pediatric dysphagia, including all members of the Interdisciplinary Feeding Team at Cincinnati Children's Medical Center. These experts present an in-depth description of their roles in the diagnosis and management of dysphagic children, providing the reader with an understanding of why a multidisciplinary model of care is key to the optimization of outcomes"--